Energetic processes regulating the strength of MJO circulation over the Maritime Continent during two types of El Niño - Pang-Chi HSU; Zhen FU; Ting XIAO (Atmospheric and Oceanic Science Letters, 2018)
The zonal shift of SST warming patterns associated with the eastern Pacific (EP) and central Pacific (CP) El Niño leads to a significant contrast in MJO strength over the Maritime Continent. The MJO circulation tends to be stronger over the Maritime Continent during the mature phase (autumn-winter) of CP El Niño than of EP El Niño. Based on a new MJO kinetic energy (KE) budget equation, in which the effects of mean flow and high-frequency disturbances on the MJO are separated, we found that the low-level MJO gains more KE from the background mean flow during CP El Niño events, although at the same time the enhanced MJO transfers more KE to high-frequency eddies. Among the three-dimensional circulation anomalies, the low-level convergence and cyclonic anomalies associated with upward anomalies of the Walker circulation over the Maritime Continent play leading roles in inducing the enhanced barotropic energy conversion from mean flow to MJO during CP El Niño events relative to EP El Niño events. The more vigorous MJO with strengthened vertical motion and heating anomalies at the upper troposphere can maintain its amplitude through the baroclinic energy conversion from the MJO available potential energy to KE. Both the low-to-mid tropospheric barotropic energy conversion from mean flow to MJO and upper-level baroclinic energy conversion contribute positively to the enhanced MJO over the Maritime Continent during CP El Niño years compared to during EP El Niño years.